PARTISIPASI DAN KESIAPAN LEMBAGA PENDIDIKAN TINGGI MEMASUKI ERA MASYARAKAT EKONOMI ASEAN (MEA) (Gagasan Rektor) - A. Dirwan (JURNAL MITRA MANAJEMEN, 2016)
ABSTRACTAlong with the reality in the era of globalization, education has been entered on one ofthe international commodities, based on several studies that Indonesia will faceincreasing challenges in the global competition. Globalization of education are difficultto avoid, so that higher education institutions in various parts of the world, includingIndonesia, supposedly able to adjust themselves to become involved in the process.Although it can be said education globalization as an inevitability, stakeholders need tobe prepared, so that education is not only the effects of globalization talkative followglobal dynamics.